Genome‐wide association study of a nicotine metabolism biomarker in African American smokers: impact of chromosome 19 genetic influences. (2nd November 2017) - Chenoweth, Meghan J.; Ware, Jennifer J.; Zhu, Andy Z. X.; Cole, Christopher B.; Cox, Lisa Sanderson; Nollen, Nikki; Ahluwalia, Jasjit S.; Benowitz, Neal L.; Schnoll, Robert A.; Hawk, Larry W.; Cinciripini, Paul M.; George, Tony P.; et al.
Abstract: Background and aims: The activity of CYP2A6, the major nicotine‐inactivating enzyme, is measurable in smokers using the nicotine metabolite ratio (NMR; 3′hydroxycotinine/cotinine). Due to its role in nicotine clearance, the NMR is associated with smoking behaviours and response to pharmacotherapies. The NMR is highly heritable (~80%), and on average lower in African Americans (AA) versus whites. We previously identified several reduce and loss‐of‐function CYP2A6 variants common in individuals of African descent. Our current aim was to identify novel genetic influences on the NMR in AA smokers using genome‐wide approaches. Design: Genome‐wide association study (GWAS). Setting: Multiple sites within Canada and the United States. Participants: AA smokers from two clinical trials: Pharmacogenetics of Nicotine Addiction Treatment (PNAT)‐2 (NCT01314001; n  = 504) and Kick‐it‐at‐Swope (KIS)‐3 (NCT00666978; n  = 450). Measurements: Genome‐wide SNP genotyping, the NMR (phenotype) and population substructure and NMR covariates. Findings: Meta‐analysis revealed three independent chromosome 19 signals (rs12459249, rs111645190 and rs185430475) associated with the NMR. The top overall hit, rs12459249 ( P  = 1.47e‐39; beta = 0.59 per C (versus T) allele, SE = 0.045), located ~9.5 kb 3′ of CYP2A6, remained genome‐wide significant after controlling for the common (~10% in AA) non‐functional CYP2A6*17 allele. In contrast, rs111645190 and rs185430475 were not genome‐wide significant when controlling for CYP2A6*17 . In total, 96 signals associated with the NMR were identified; many were not found in prior NMR GWASs in individuals of European descent. The top hits were also associated with the NMR in a third cohort of AA (KIS2; n  = 480). None of the hits were in UGT or OCT2 genes. Conclusions: Three independent chromosome 19 signals account for ~20% of the variability in the nicotine metabolite ratio in African American smokers. The hits identified may contribute to inter‐ethnic variability in nicotine metabolism, smoking behaviours and tobacco‐related disease risk.